PENGARUH MODEL PEMBELAJARAN THINK TALK WRITE (TTW) BERBANTUAN MEDIA FLIPBOOK “BUDARIER” TERHADAP PEMAHAMAN KONSEP IPAS SISWA SD - Novita, Elsa; Yuni Purwanti, Kartika (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
ABSTRACT This study aims to determine the effect of implementing the Think-Talk-Write (TTW) learning model, supported by "BUDARIER" flipbook media, on the understanding of IPAS (Natural and Social Sciences) concepts among elementary school students. This study employs a quantitative quasi-experimental approach using a non-equivalent control group design. The population consisted of all students from SDN 03 Pringapus and SDN 01 Klepu; the sample was selected via purposive sampling, with the Grade IV class at SDN 03 Pringapus serving as the experimental group and the Grade IV class at SDN 01 Klepu as the control group. Data collection involved concept understanding tests, lesson implementation observation sheets, and student response questionnaires. Data analysis techniques included prerequisite tests (normality and homogeneity tests) and hypothesis testing using the Independent Sample T-Test and simple linear regression. The analysis results indicate that: (1) there is a significant difference in IPAS concept understanding between the experimental group—using the TTW model with "BUDARIER" flipbook media—and the control group; and (2) the implementation of the TTW learning model supported by "BUDARIER" flipbook media has a positive and significant effect on students' understanding of IPAS concepts. Thus, the combination of the TTW model and "BUDARIER" flipbook media is effective in enhancing the quality of students' concept understanding regarding cultural diversity material.